CHARACTERIZATION OF TECHNOLOGY-DEPENDENT PATIENTS IN HOME CARE SERVICES - Cecília Maria Brondani; Lais Helena Ramos; Margrid Beuter; Melissa Agostini Lampert; Margot Agathe Seiffert; Jamile Lais Bruinsma (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211063 Aim: to characterize the technology-dependent patients cared for in home care services of a University Hospital in the central region of Rio Grande do Sul, Brazil. Method: quantitative research, with descriptive and cross-sectional design developed with 57 patients dependent on technologies at home. The data were submitted to descriptive statistical analysis. Results: it was found that most patients were male, married, average age of 58 years, low income and education and made use of more than a technological device. And 73.7% used probes to aid in feeding, 24.6% tracheostomy and 22.8% oxygen. It was identified that 56.2% were discharged, 26.3% another hospitalization and 17.5% died. Conclusions: we need to consider that an increasing number of people use technologies at home. Health professionals should be attentive to the health needs of these people making comprehensive and continuous care.